Medico-legal evidence collection in child sexual assault cases: a forensic significance - Suminder Kaur (SpringerOpen, 2021)
Abstract Background Every year, millions of children face sexual exploitation worldwide. In India, 109 children (National Crime Records Bureau2018) were sexually abused everyday (22% jump from the previous year). Even with advanced DNA techniques, the conviction rate remains low. The methods used for forensic DNA evidence analysis vary around the world, but the primary step of biological evidence collection plays the most vital role. Proper and timely evidence collection from the victim by a trained medical professional is important. Main body Dynamics of child sexual assault being massively different from an adult rape demands altogether different approach of evidence collection. A standard sexual kit employed for evidence collection needs urgent modifications considering genital development of pre- and post-pubertal victims. In the present study, parameters including systemic collection and evaluation of forensic evidences, medico-legal examination, and developmental consequences of sexual assault on pre-pubertal victims were assessed. Further suggestions for separate evidence collection kit during medico-legal examination were given for pre-pubertal victims and alleged accused in sexual assault cases in order to streamline and for better evaluation of DNA analysis in forensic laboratories. Conclusion The importance of expert medical practitioners plays a significant role in collection of appropriate information and evidences from the victim of sexual assault. General guidelines for evidence collection in sexual assault cases are not well suited for pre-pubertal victims. Appropriate reforms pertaining to the age and genital development of victims are required. Securing clothing as forensic evidence is essential in most cases as it turned out to be the exclusive evidence bearing material. The purpose of this article is to bring awareness about the thorough medical examination and modified sexual assault kit for pre-pubertal victims and alleged accused for a better approach in evidence collection and conviction rate.